3D Concrete Printing Sustainability: A Comparative Life Cycle Assessment of Four Construction Method Scenarios - Malek Mohammad (17150977) (2020)
Three-dimensional concrete printing (3DCP) has become recognized as a possible alternative to conventional concrete construction, mainly due to its potential to increase productivity and reduce the environmental impact of the construction industry. Despite its up-and-coming popularity within the field, limited research has quantitively investigated the environmental benefits that 3DCP brings. This paper investigates the environmental tradeoff of utilizing 3DCP over conventional construction by conducting a detailed cradle-to-gate life cycle assessment (LCA) study of four case-scenarios (conventional concrete construction, 3DCP with reinforcement elements, 3DCP without any reinforcement, and 3DCP without any reinforcement and utilizing a lightweight printable concrete material.) These case-scenarios were carefully selected to quantify the environmental impact of 3DCP while emphasizing the importance of the material composition. The LCA was conducted for a 1 m2 external load-bearing wall in all four scenarios. The LCA analysis showed that 3DCP significantly reduced environmental effects in terms of global warming potential (GWP), acidification potential (AP), eutrophication potential (EP), smog formation potential (SFP), and fossil fuel depletion (FFD), as compared to conventional construction methods. However, these environmental improvements diminished when 3DCP was coupled with the use of conventional reinforcement elements. Moreover, the use of an alternative concrete mixture in 3DCP showed a further decrease in the GWP, AP, EP, and FFD impact. Ultimately, the findings in this paper support the advantages of 3DCP technology and recommend the investigation of the development of (i) sustainable printable concrete materials and (ii) novel reinforcement techniques that are suitable for 3DCP rather than adopting conventional reinforcement techniques. Other Information Published in: Buildings License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/buildings10120245 Additional institutions affiliated with: Mechanical Engineering Program - TAMUQ